2017
DOI: 10.4028/www.scientific.net/amm.869.9
|View full text |Cite
|
Sign up to set email alerts
|

Viscous Fingering: A Topological Visual Analytic Approach

Abstract: Abstract.We present a methodology to analyze and visualize an ensemble of finite pointset method (FPM) simulations that model the viscous fingering process of salt solutions inside water. In course of the simulations the solutions form structures with increased salt concentration called viscous fingers. These structures are of primary interest to domain scientists as it is not clear when and where viscous fingers appear and how they evolve. To explore the aleatoric uncertainty embedded in the simulations we an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…1). Fingers can be identified algorithmically by first sampling the salt concentration density of the pointsets on a regular grid and then deriving superlevel set components below the salt supply [17]. Lukasczyk et al [19] demonstrated that NTGs can be used to effectively summarize shared properties of the fingers across different runs, timesteps, and initial parameters.…”
Section: Viscous Fingeringmentioning
confidence: 99%
“…1). Fingers can be identified algorithmically by first sampling the salt concentration density of the pointsets on a regular grid and then deriving superlevel set components below the salt supply [17]. Lukasczyk et al [19] demonstrated that NTGs can be used to effectively summarize shared properties of the fingers across different runs, timesteps, and initial parameters.…”
Section: Viscous Fingeringmentioning
confidence: 99%
“…Oftentimes, these approaches require the presence of clearly defined features in isomorphic structures, and are not directly relevant to our illustrative example: finger structures are soft-knowledge features. Favelier et al [21] and Lukasczyk et al [37] use an adaptation of Shepard's kernel method [59] to identify such features based on concentrations. Both these works rely on userdefined thresholds.…”
Section: Cfd Visualizationmentioning
confidence: 99%
“…Basic visual abstractions such as line charts, quartile charts, and histograms are commonly used in ensemble visualization to encode statistical parameters [28], as well as reduced spatial aggregate views [19,37] to display specific attributes at a specific time and location. To facilitate further exploration of ensemble members across space and time, these aggregate views are linked to range-based representations [26].…”
Section: Cfd Visualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Its applicability to time-varying data [10,91], ensembles [35] and comparisons [92] makes it a reliable candidate for assessing the likeliness of simulations in an ensemble given a ground truth. Although several approaches have explored the promising potential of TDA for extracting and characterizing the features of interest in viscous fingering simulations [36,59], no approach has been proposed to estimate the similarity between two time-varying viscous fingerings based on topological representations.…”
Section: Introductionmentioning
confidence: 99%